2018
DOI: 10.1002/jlb.5ru0718-276rr
|View full text |Cite
|
Sign up to set email alerts
|

Immune rebalancing by oral immunotherapy: A novel method for getting the immune system back on track

Abstract: Immune modulating treatments are often associated with immune suppression or an opposing anti‐inflammatory paradigm. As such, there is a risk of exposing patients to infections and malignancies. Contrarily, eliciting only mild immune modulation can be insufficient for alleviating immune‐mediated damage. Oral immunotherapy is a novel approach that uses the inherent ability of the gut immune system to generate signals that specifically suppress inflammation at affected sites, without inducing generalized immune … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 115 publications
(233 reference statements)
1
13
0
Order By: Relevance
“…Sphingolipids (SLs), as a class of bioactive lipids, are the main structural components of the cell membrane ( Kraft, 2017 ). SLs mainly include ceramide, sphingosine and sphingosine-1-phosphate, which participate in the occurrence and development of liver diseases by regulating cell proliferation and differentiation, gene expression and apoptosis ( Ilan, 2019 ). Studies have shown that liver injury can lead to the disturbance of sphingosine metabolism and significant changes of the related substances ( Acunha et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…Sphingolipids (SLs), as a class of bioactive lipids, are the main structural components of the cell membrane ( Kraft, 2017 ). SLs mainly include ceramide, sphingosine and sphingosine-1-phosphate, which participate in the occurrence and development of liver diseases by regulating cell proliferation and differentiation, gene expression and apoptosis ( Ilan, 2019 ). Studies have shown that liver injury can lead to the disturbance of sphingosine metabolism and significant changes of the related substances ( Acunha et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…The present data support CD1d + lymphocyte plasticity which underlines the differences noted between the different models. NKT cells were shown to be either useful or associated with liver damage under different conditions in an environment-and/or disease-dependent manner 47,48 . GC treatment alleviates immunologically incongruous disorders, suggesting it is associated with a " ne tuning" of immune responses by altering NKT-plasticity 48,49 , and this effect may be CD1d-mediated 50,51 .…”
Section: Discussionmentioning
confidence: 99%
“…The gut provides a platform for generating immune signals that impact the systemic immune system 95 , 96 , 97 . Adjuvants, including non-absorbable compounds, have been used to modulate the intestinal immune signals in several preclinical and clinical trials using non-absorbable compounds 95 , 96 , 97 , 98 , 99 , 100 , 101 , 102 , 103 , 104 , 105 .…”
Section: Augmenting the Antiviral Cellular Immune Response And Mitigating The Immune-mediated Target Organ Damage Using An Adjuvant Appromentioning
confidence: 99%
“…The gut provides a platform for generating immune signals that impact the systemic immune system 95 , 96 , 97 . Adjuvants, including non-absorbable compounds, have been used to modulate the intestinal immune signals in several preclinical and clinical trials using non-absorbable compounds 95 , 96 , 97 , 98 , 99 , 100 , 101 , 102 , 103 , 104 , 105 . Three types of adjuvants, namely glycosphingolipids, low-dose colchicine, and hyperimmune colostrum that target the gut immune system have been proposed to augment the antiviral immune response and mitigate immune-mediated target organ damage in patients with COVID-19.…”
Section: Augmenting the Antiviral Cellular Immune Response And Mitigating The Immune-mediated Target Organ Damage Using An Adjuvant Appromentioning
confidence: 99%